2020
DOI: 10.2341/19-002-l
|View full text |Cite
|
Sign up to set email alerts
|

How Do the Etching Mode and Thermomechanical Loading Influence the Marginal Integrity of Universal Adhesives?

Abstract: SUMMARY Objective: This study evaluated the effect of etching mode and thermomechanical loading on universal adhesives. Methods and Materials: Two universal adhesives, Peak Universal and Adhese Universal, were used in two etching modes as the experimental groups: Peak Universal etch-and-rinse (PER), Peak Universal self-etch (PSE), Adhese Universal etch-and-rinse (AER), and Adhese Universal se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Moreover, mechanical loading causes tooth and filling deformations, which lead to increases in existing gaps or the development of new gaps at the tooth-filling interface [16,17,33]. Unfortunately, there is a lack of standardized TML protocols; however, the parameters used in this study were successfully implemented in previous studies [7,22,33]. Water storage is an easier and cheaper method but more time-consuming than thermocycling or mechanical loading; however, the combination of those three aging methods can reproduce the conditions in the oral cavity [34].…”
Section: Thermomechanical Loading (Tml) and Water Degradation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, mechanical loading causes tooth and filling deformations, which lead to increases in existing gaps or the development of new gaps at the tooth-filling interface [16,17,33]. Unfortunately, there is a lack of standardized TML protocols; however, the parameters used in this study were successfully implemented in previous studies [7,22,33]. Water storage is an easier and cheaper method but more time-consuming than thermocycling or mechanical loading; however, the combination of those three aging methods can reproduce the conditions in the oral cavity [34].…”
Section: Thermomechanical Loading (Tml) and Water Degradation Analysismentioning
confidence: 99%
“…Destructive methods use a tracer or dye and damage the sample by cutting it into sections to visualize the extent of staining along the tooth-filling interface using methods such as light microscopy, scanning electron microscopy (SEM), or optical microscopy [20,21]. Exemplary non-destructive methods are the replica technique in combination with SEM for external marginal adaptation [7,22] or X-ray micro-computed tomography (µCT) analysis [21,23]. This three-dimensional (3D) method enables the detection of all internal gaps and irregularities as well as their changes over time.…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro studies have been conducted to evaluate characteristics of universal adhesives (5)(6)(7)(8). Etching mode and thermomechanical loading significantly influenced the marginal integrity of universal adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…In dentin, the greatest percentage of continuous Original Article Clinical effects of different etching modes for universal adhesives: a systematic review and meta-analysis margin was achieved for Adhese Universal in the ER group (100%) before TML and for both universal adhesives in the SE groups (61%) after TML. Thermomechanical loading did not influence the margin integrity in the enamel, while it did influence the margin integrity in dentin (6). Diniz et al found that etch-and-rinse approach lead to higher bond strength of enamel compared with self-etch approach (9).…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 9 ] Furthermore, universal adhesive systems combine the advantages of these two etching strategies, which simplify and accelerate the adhesive application. [ 10 ] However, the behavior of universal adhesives to dentin impregnated with endodontic sealers is still uncertain.…”
Section: Introductionmentioning
confidence: 99%